Problems of Post-War Restoration and Development of Infrastructure in Ukraine - Amosha, O.; Amosha, O. (Економічний вісник Донбасу, 2023)
The article draws attention to the lack of a key formula in strategic planning for the development of recovery programs. Therefore, the possibility of infrastructure transformation as a key component of the formula for economic recovery is considered. The role of infrastructure in the conditions of war and after it is analyzed. The importance of infrastructure for economic recovery, social sphere and national security is emphasized, taking into account large losses in various areas, such as housing, transport, industry, education, health and others. Developing effective recovery programs with a focus on infrastructure has been shown to be crucial. Final decisions should be based on careful analysis, impact assessment, and clear strategic planning based on historical experience. The article draws attention to the lack of a key formula in strategic planning for the development of recovery programs. Therefore, the possibility of infrastructure transformation as a key component of the formula for economic recovery is considered. The role of infrastructure in the conditions of war and after it is analyzed. The importance of infrastructure for economic recovery, social sphere and national security is emphasized, taking into account large losses in various areas, such as housing, transport, industry, education, health and others. Developing effective recovery programs with a focus on infrastructure has been shown to be crucial. Final decisions should be based on careful analysis, impact assessment, and clear strategic planning based on historical experience.